HUBUNGAN PELAKSANAN KOMUNIKASI TERAPEUTIK DENGAN TINGKAT KECEMASAN PASIEN RAWAT INAP DI BP RSUD KEBUMEN - ike mardiati agustin (Jurnal Ilmiah Kesehatan Keperawatan, 2009)
The prevalences of  patients′ anxiety in the medical world are varied between 17% up to 27% depend on the diagnostic used. Based on the introduction study in January 2006 of 10 patients and their families in long stay ward of BP RSUD Kabumen, there were nurses who hadn′t given optimal communication so the patients families got information in completly. It made the patient′s anxiety before the operation increase. The goals of the research are to describe major pre operation patients characteristic, to describe Therapeutic communication application done by the nurses, to describe the anxiety level of the major pre operation patients, and to prove how the correlation between the theurapeutic communication aplication with the major pre operation patients anxiety level in the long stay wards of BP RSUD Kebumen. This is a correlational descriptive research. The data were gained by using sectional method. The samples were taken by using purposive sampling technique. There were 30 major pre operation patients in the long stay wards of BP RSUD Kebumen taken as samples. The data were analysed descriptively and then the Sperman Rho Test was done with level of significant (0,05). The research found that there were 13 respondents ( 43,33%)  were graduated from elementary schools, 13 respondents ( 43,33%) were girls, and 12 respondents (40%) were > 40 years old. Based on the study in the long stay wards of BP RSUD Kebumen, there were 13 nurses ( 43,33%) had good enough Therapeutic communication application result, and there were 18 respondents of the major pre operation patients (60%) had medium anxiety level. Sperman Rho test showed that p table result ( 0,0560) > count p (0,5) whith the significant level 0.05. It can be concluded from the research that the nurses theurapeutic communication aplication had good enough and the major pre operation patients had medium anxiety level. So there was meaningful correlation between therapeutic communication application and the major pre operation patients anxiety in the long stay wards of General Hospital Kebumen.   Keywords : Therapeutic communication, anxiety, pre operation